2022
DOI: 10.1155/2022/8077058
|View full text |Cite|
|
Sign up to set email alerts
|

Dioscorea nipponica Makino Relieves Ovalbumin-Induced Asthma in Mice through Regulating RKIP-Mediated Raf-1/MEK/MAPK/ERK Signaling Pathway

Abstract: Purpose. Dioscorea nipponica Makino (DNM) is a traditional herb with multiple medicinal functions. This study is aimed at exploring the therapeutic effects of DNM on asthma and the underlying mechanisms involving RKIP-mediated MAPK signaling pathway. Methods. An ovalbumin-induced asthma model was established in mice, which was further administrated with DNM and/or locostatin (RKIP inhibitor). ELISA was performed to detect the serum titers of OVA-IgE and OVA-IgG1, bronchoalveolar lavage fluid (BALF) levels of i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 42 publications
0
4
0
Order By: Relevance
“…The sensitizing doses utilized in current murine studies typically range from 10 to 100 μg 7,17–19 . However, the effects of various doses within this range have not been thoroughly investigated.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The sensitizing doses utilized in current murine studies typically range from 10 to 100 μg 7,17–19 . However, the effects of various doses within this range have not been thoroughly investigated.…”
Section: Discussionmentioning
confidence: 99%
“…The sensitizing doses utilized in current murine studies typically range from 10 to 100 μg. 7 , 17 , 18 , 19 However, the effects of various doses within this range have not been thoroughly investigated. In 1999, Sakai et al 20 demonstrated the impact of sensitive OVA doses (0, 10, 100, and 1000 μg) on AHR; their study suggested that sensitization with a dose of 10 μg may be more effective than with a dose of 100 μg but almost completely inhibited at a dose of 1000 μg.…”
Section: Discussionmentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Manipulated or compromised peer review …”
mentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%